2013
DOI: 10.1038/srep01452
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium-fluctuation-analysis of single liposome binding events reveals how cholesterol and Ca2+ modulate glycosphingolipid trans-interactions

Abstract: Carbohydrate−carbohydrate interactions (CCIs) are of central importance for several biological processes. However, the ultra-weak nature of CCIs generates difficulties in studying this interaction, thus only little is known about CCIs. Here we present a highly sensitive equilibrium-fluctuation-analysis of single liposome binding events to supported lipid bilayers (SLBs) based on total internal reflection fluorescence (TIRF) microscopy that allows us to determine apparent kinetic rate constants of CCIs. The lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 53 publications
(89 reference statements)
6
29
0
Order By: Relevance
“…Our simulations employ a recent carbohydrate force field 30 that allows a more faithful representation of carbohydrate-carbohydrate interactions [30][31][32] and exceed the times and system sizes in previous simulation studies of carbohydrate-carbohydrate interactions in solution [33][34][35] by orders of magnitude. Le X has been investigated extensively as a model system for carbohydrate-carbohydrate interactions, 13,14,16,[19][20][21]23 and experimental data available from these investigations are central to corroborate our simulation results. In our Le X glycolipids, the Le X trisaccharide is connected via a lactose disaccharide and a glycerol linker to lipids tails (see Fig.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our simulations employ a recent carbohydrate force field 30 that allows a more faithful representation of carbohydrate-carbohydrate interactions [30][31][32] and exceed the times and system sizes in previous simulation studies of carbohydrate-carbohydrate interactions in solution [33][34][35] by orders of magnitude. Le X has been investigated extensively as a model system for carbohydrate-carbohydrate interactions, 13,14,16,[19][20][21]23 and experimental data available from these investigations are central to corroborate our simulation results. In our Le X glycolipids, the Le X trisaccharide is connected via a lactose disaccharide and a glycerol linker to lipids tails (see Fig.…”
Section: Introductionsupporting
confidence: 62%
“…Several groups have reported that Le X binding depends on Ca 2+ , 13,14,[19][20][21]54,55 whereas other groups have observed no dependence on Ca 2+ . 16,23 As pointed out by Kunze et al, 21 the Ca 2+ concentrations used by most groups are of the order of 10 mM and, thus, greatly beyond physiological Ca 2+ concentrations. In vesicle adhesion experiments, Kunze et al 21 observed a rather small increase of the number of bound vesicles for a physiological Ca 2+ concentration of 0.9 mM, compared to experiments in the absence of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experimental approach, the residence time of bound virions can be collected for each individual Initial work monitoring nanoparticle binding to supported bilayers and surfacetethered vesicles demonstrated the advantage of using TIRF microscopy in this application. Here, a useful approach, equilibrium-fluctuation-analysis, was developed to quantify apparent kinetic rate constants of carbohydrate-bearing particles with carbohydrate presenting SLBs [80]. This analysis was then extended to studies of virus-like particles [49,81] and live virions [81] interacting with glycosylated bilayers to provide new insight into virus attachment to cell surfaces and applications in biosensing [82].…”
Section: Single Virion Tracking Of Bindingmentioning
confidence: 99%
“…For a better understanding of the functional mechanisms relevant to oligosaccharides on cell membranes, it is desirable to develop appropriate models of their clusters . For characterizing carbohydrate–carbohydrate interactions, various glycoclusters have been fabricated by accumulation of carbohydrates on artificial scaffolds such as polymers, nanoparticles, and liposomes, and characterized using analytical techniques such as transmission electron microscopy, atomic force microscopy, and surface plasmon resonance measurements . However, the physicochemical and structural properties of carbohydrate clusters remain largely unknown, primarily because of the lack of an appropriate glycocluster model system that combines structural homogeneity and the functional ability to promote carbohydrate–carbohydrate interactions.…”
Section: Figurementioning
confidence: 99%